Visualizing and Mapping Two Decades of Literature on Corporate Tax: A Bibliometric Analysis - Noor Emilina Mohd Nasir; Najihah Marha Yaacob; Norfadzilah Rashid; Siti Nurhazwani Kamarudin (Universitas Pasundan, 2023)
This study aims to identify and present current trends in worldwide research on corporate taxation using bibliometric methods. A comprehensive search was conducted in the Scopus database for all publications in the field of corporate tax research from 2003 to 2022. The bibliographic profiles were used for further searches on corporate tax, which included 813 scholarly articles recorded in the Scopus database through August 2022. In addition, Harzing’s Publish or Perish software was used to analyze the citation profiles. In a final step, VOSviewer software was used to visualize and map research outputs using bibliometric networks. The results show an increasing research trend in the field of corporate taxes. One of the main keywords in this area was tax avoidance. The study contributes to the existing body of knowledge by providing a comprehensive analysis of research trends in corporate taxation published in the Scopus database for over two decades.